Sulfur-assisted synthesis of indium nitride nanoplates from indium oxide. Issue 100 (14th October 2016) - Wang, Liangbiao; Pan, Yanxia; Shen, Qianli; Zhang, Junhao; Bao, Keyan; Lou, Zhengsong; Zhao, Dejian; Zhou, Quanfa
Abstract : Indium nitride (InN) is much more difficult to prepare than other group III nitrides for its low thermal stability. Abstract : Indium nitride (InN) is much more difficult to prepare than other group III nitrides for its low thermal stability. Here, InN nanoplates are prepared by using In2 O3, NaNH2 and sulfur as starting materials in a stainless steel autoclave at 190 °C. This method has the advantages of requiring a low temperature and without using an ammonia flow. Field-emission scanning electron microscope shows that the length of InN nanoplates is about 400 nm with the thickness of 50 nm. Finally, the formation mechanism is also investigated.